The Baltic States' integration into the European division of labour - Claus-Friedrich Laaser; Klaus Schrader (Kiel Institute for World Economics (IfW), 2004)
The analysis of Baltic trade statistics and gravity estimates reveal that Estonia, Latvia and Lithuania have rapidly integrated into the international division of labour with a distinct EU focus. The Baltic States have taken a road towards the EU common market which pays particular attention to close trade relations with their immediate neighbours in the Baltic Sea Region. The Baltic Sea obviously serves as a major integrating device for these countries. At the same time the Baltic States, although being no longer integrated into the former intra-Soviet division of labour, have not abandoned their contacts to the Soviet successor states altogether. Accordingly, they still have the potential to serve as a gateway from Europe to the CIS markets.
Keywords: N74; F14; F15; 330; Eastern enlargement; Regional integration; Gravity model; Baltic trade patterns; Internationale Arbeitsteilung; Gravitationsmodell; Internationale Wirtschaftsbeziehungen; Nordosteuropa; Estland; Lettland; Litauen; EU-Staaten; GUS-Staaten